(untitled) (Ozone Therapy Global Journal, 2018)
Sacroilitis is an inflammation of the sacroiliac joint and constitutes 15 % of the causes of low back pain and pain radiating down the leg, mimicking sciatica, which is difficult to diagnose and even more relieved with allopathic therapies. The objective of this research was to evaluate the efficacy of ozone therapy injections in the treatment of this condition. Seventy-five patients who were seen at private office in the city of Culiacan, Sinaloa, Mexico between August 2012 and January 2007, were included in the experimental data. For treatment, the sacroiliac joint was approached (2-3) mL of procaine 0.3 % in the inlet area and then 20 mL of the O3/O2 mixture at a concentration of 10 μg/mL was injected in the joint and the ligamentary system and 10mL in the outlet area. The procedures were done once a week.The number of injections varied from 1 to 21 sessions, media value 5, depending on the clinical outcome and patient satisfaction with this therapeutic procedure. To evaluate the effect of ozone therapy on pain and disability were applied the visual analog scale (VAS) and the Roland Morris Disability Questionnaire. Patient satisfaction was also assessed using the modified MacNab Criterion. Applying the nonparametric signed rank Wilcoxon test showed significant difference for the three studied tests. It was made correlations between variables and found that there was a significant correlation between body mass index, initial VAS and the number of treatment sessions, so overweight and obesity are risk factors for developing sacroilitis and also to alleviate it. There were no adverse reactions. No publication was found on the application of ozone therapy to sacroilitis, so this report can be considered as an initial contribution to the specialized literature in this medicine field. Finally, it was concluded that ozone therapy is an effective, simple and safe way to improve pain and disability of patients with sacroilitis, and it may be an alternative therapy in this condition